Structurally abnormal collagen fibrils in abdominal aortic aneurysm resist platelet adhesion. (9th November 2021) - Jones, Blain; Debski, Anna; Hans, Chetan P.; Go, Michael R.; Agarwal, Gunjan
Abstract: Background: Platelet adhesion to the subendothelial collagen fibrils is one of the first steps in hemostasis. Understanding how structural perturbations in the collagen fibril affect platelet adhesion can provide novel insights into disruption of hemostasis in various diseases. We have recently identified the presence of abnormal collagen fibrils with compromised D‐periodic banding in the extracellular matrix remodeling present in abdominal aortic aneurysms (AAA). Objective: In this study, we employed multimodal microscopy approaches to characterize how collagen fibril structure impacts platelet adhesion in clinical AAA tissues. Methods: Ultrastructural atomic force microscopy (AFM) analysis was performed on tissue sections after staining with fluorescently labeled collagen hybridizing peptide (CHP) to recognize degraded collagen. Second harmonic generation (SHG) microscopy was used on CHP‐stained sections to identify regions of intact versus degraded collagen. Finally, platelet adhesion was identified via SHG and indirect immunofluorescence on the same tissue sections. Results: Our results indicate that ultrastructural features characterizing collagen fibril abnormalities coincide with CHP staining. SHG signal was absent from CHP‐positive regions. Additionally, platelet binding was primarily localized to regions with SHG signal. Abnormal collagen fibrils present in AAA (in SHG negative regions) were thus found to inhibit platelet adhesion compared to normal fibrils. Conclusions: Our investigations reveal how the collagen fibril structure in the vessel wall can serve as another regulator of platelet–collagen adhesion. These results can be broadly applied to understand the role of collagen fibril structure in regulating thrombosis or bleeding disorders.